Socio-Demographic Factors in Influencing the Role of Bully and Victim among the Malay Female Juvenile Detainees in Rehabilitation Centre before Detention - Junainor Hassan; Hassad Hassan; Nor Syamimi Mohamed Adnan; Siti Norayu Mohd Basir, (Journal of Human Development and Communication (JoHDeC), 2025)
This study examines the socio-demographic factors in influencing the role of bully and victim among the Malay female juvenile detainees before detention in a rehabilitation centre. This is a quantitative study which uses descriptive and correlation analysis. The study was done in one of the single-sex rehabilitation centres up north of Malaysian state. There were n=30 Malay female juvenile detainees involved in this study (n=4 Malay female juvenile detainees aged 19; n=4 respondents aged 18; n=8 respondents aged 17; n=6 respondents aged 16; n=3 respondents aged 15; n=2 respondents aged 14 and, n=3 respondents aged 13 years old). Self builds demographic questionnaire and Olweus Bullying Behaviour Questionnaire (BBQ). The Cronbach's alpha for BBQ was 0.867 with the role of bully scores on .0798 and role of victims scores on .815. The finding in this study shows the strongest correlation between the role of bully by the Malay female juvenile detainees were parent’s or guardian’s source of income (r=.759,p<0.01); the education and academic achievements of the Malay female juvenile detainees (r=.756,p<0.01); followed by residencies (r=.702,p<0.01) and, parent’s or guardian’s level of education (r=.609,p<0.01). As for the role of victim; the strongest correlation was found between education and academic achievements of the Malay female juvenile detainees (r=.848,p<0.01); parent’s or guardian’s source of income (r=.778,p<0.01); residencies (r=.728,p<0.01) and, parent’s or guardian’s level of education (r=.656,p<0.01). Socio-demographic factor is an important influence factor for a young adolescent to take up the role of bully and victim in any bullying behaviour scenarios. These socio-demographic influence factors must be taken into consideration in studying bullying behaviour cases especially in designing any prevention programme or correctional programme.